Improving the prevention of fall from height on construction sites through the combination of technologies - Rey-Merchán, María del Carmen; Gómez-de-Gabriel, Jesús Manuel; Fernández-Madrigal, Juan Antonio; López-Arquillos, Antonio (Taylor&Francis, 2020)
Fall from height is a cause of concern in the construction sector. Appropriate use of a harness can be the difference between an incident or a critical accident. Monitoring the proper use of a harness in the workplace using Bluetooth Low Energy (BLE) devices is a recent and effective approach. The aim of this article is to identify typical limitations in a BLE monitoring system in order to propose solutions according to the existing literature. Alternative solutions found in the literature showed that the integration of BLE with other technologies such as building information modeling, radio-frequency identification or the global positioning system can improve the effectiveness of current monitoring approaches based only on BLE and reduce rates of fall from height accidents. For correct integration, both technological factors (cost, compatibility, data transmission) and cultural factors (social acceptance, procedures, etc.) must be taken into account.
Keywords: Trabajo - Medidas de seguridad; Construction safety; Fall from height; Harness; Beacon; Safety at work